Принципи формування організаційно-економічного механізму управління інноваційними процесами та методичні основи вибору варіантів інноваційного розвитку підприємства - Карпович, О. М. (Ways to Improve Construction Efficiency, 2013)
The principles of organizational-economic mechanism of the enterprise innovation processes, organizational and economic mechanism of management of innovative development, teaching the basics of choice options Innovation Development Company.